P45 Investigating the feasibility of an on-line health resource integrated with nurse coach support for those with advanced COPD. (14th November 2013) - Young, J; Early, F; Homan, K; Fuld, J; Wisbauer, S
Abstract : Background: Self-management may improve health status in chronic disease. It is not routinely embedded into COPD care. Pulmonary rehabilitation provides behaviour change opportunities but is not available to all. Aims: To test the feasibility of a combined intervention (online health resource 'The Prevention Plan' (TPP) with nurse coach support) with a key aim to identify impact on activation for self-management. Secondary outcomes of interest were health-related quality of life, emotional functioning, information needs and exercise capacity. Method: 17 patients were recruited (FEV1 < 75% predicted (range 15–74, mean 38.01, SD 17.92). Hardware and internet access were provided. Patients had unlimited access to TPP, home visits, telephone contacts and email with the nurse coach. The nurse coach supported behaviour change through patient-led goal setting and techniques to enhance self-efficacy. Outcomes were followed up at 9–29 weeks (mean = 15) after joining the programme. Measures were patient activation (PAM), health-related quality of life (CRQ), anxiety and depression (HADS), information needs (LINQ) and GAIT test. Semi-structured interviews were conducted. Qualitative analysis is underway and results will be reported separately. Results: Mean age was 61.4 years (range 46 to 79), 9 female, 8 male. 14 patients completed follow-up assessments. 1 patient withdrew due to illness and two were unable to complete follow-up. Statistically significant improvement was found for activation (p = 0.0035, t = 3.56, df = 13), CRQ-fatigue (p = 0.0427, t = 2.25, df = 13), anxiety (p = 0.0444, t = 2.22, df = 13), information needs (p = 0.0001, t = 6.09, df = 13). Conclusion: The intervention supported patients to become more activated for self-management. Patients showed increased confidence to manage their condition and strengthening of belief that taking an active role in managing their COPD was important. Secondary benefits related to fatigue, anxiety and feeling more informed about COPD. Qualitative analysis will illuminate these findings and explore intervention factors that led to greatest benefit.